Poly(N,N-dimethylaminoethyl methacrylate-co-2-acrylamido-2-methyl-propanosulfonic acid)/Laponite nanocomposite hydrogels and cryogels with improved mechanical strength and rapid dynamic properties - Boyaci, Talin; Orakdogen, Nermin (Elsevier BV, 2016)
Abstract A new type of stimuli-responsive organic/inorganic nanocomposite hydrogels and cryogels was prepared by introducing Laponite into poly( N , N -dimethylaminoethyl methacrylate-co-2-acrylamido-2-methyl-propanosulfonic acid) copolymeric network. The effect of Laponite concentration on the equilibrium water and saline adsorbencies as well as the resulting mechanical properties were investigated. N , N -dimethylaminoethyl methacrylate (DMAEMA), 2-acrylamido-2-methyl-propanosulfonic acid (AMPS) and Laponite (LAP) were used as ionic monomers and inorganic component, respectively. The reactions were carried out with and without the presence of the chemical cross-linker diethylene glycol dimethacrylate (DEGDMA). The clay polymer nanocomposites (CPN) were prepared at a fixed initial monomer concentration and ionic comonomer AMPS content but at various Laponite concentration from 0 to 4.40% w/v. The swelling behavior and mechanical properties of CPN gels were compared with those of the corresponding chemically cross-linked gels. The results indicated that the introduced synthetic clay mineral could influence the physico-chemical properties of obtained nanocomposites. P(DMAEMA-co-AMPS)/Lap CPN hydrogels had much greater equilibrium-swelling ratio and P(DMAEMA-co-AMPS)/Lap CPN cryogels had significantly improved mechanical properties. As the content of Laponite increased, the elastic moduli and the effective cross-link chain density increased, while the equilibrium swelling ratio in water decreased owing to the increasing crosslinking points and the decreasing percentage of hydrophilic groups in network structure. The saline sensitivity of the P(DMAEMA-co-AMPS)/Lap CPN cryogels was investigated with different saline solutions. The effect of three salt solutions on the swelling had the following order: K +  > Na +  > Mg 2 + . This work provided a facile method to prepare stimuli-responsive nanocomposite gels with excellent mechanical strength. The properties of CPN gels could be adjusted by controlling the content of Laponite.